The Role of eNOS Phosphorylation in Causing Drug-induced Vascular Injury. (June 2014) - Tobin, Grainne A. McMahon; Zhang, Jun; Goodwin, David; Stewart, Sharron; Xu, Lin; Knapton, Alan; González, Carlos; Bancos, Simona; Zhang, Leshuai; Lawton, Michael P.; Enerson, Bradley E.; Weaver, James L.
Previously we found that regulation of eNOS is an important part of the pathogenic process of Drug-induced vascular injury (DIVI) for PDE4i. The aims of the current study were to examine the phosphorylation of eNOS in mesentery versus aorta at known regulatory sites across DIVI-inducing drug classes and to compare changes across species. We found that phosphorylation at S615 in rats was elevated 35-fold 2 hr after the last dose of CI-1044 in mesentery versus 3-fold in aorta. Immunoprecipitation studies revealed that many of the upstream regulators of eNOS activation were associated with eNOS in 1 or more signalosome complexes. Next rats were treated with drugs from 4 other classes known to cause DIVI. Each drug was given alone and in combination with SIN-1 (NO donor) or L-NAME (eNOS inhibitor), and the level of eNOS phosphorylation in mesentery and aorta tissue was correlated with the extent of vascular injury and measured serum nitrite. Drugs or combinations produced altered serum nitrite levels as well as vascular injury score in the mesentery. The results suggested that phosphorylation of S615 may be associated with DIVI activity. Studies with the species-specific A2A adenosine agonist CI-947 in rats versus primates showed a similar pattern.